Current Surgical Interventions for Treating Tuberculosis: Exploring the Benefits and Risks (Asian Journal of Pharmaceutics (AJP), 2023)
The main organs affected by the chronic infectious disease tuberculosis (TB) are the lungs. Although the main formof therapy for TB is medicinal, surgical intervention may be necessary if the disease is localized to a particulararea of the lung and cannot be effectively treated with medicines alone. Segmentectomy, pneumonectomy, andlobectomy are the three primary surgical procedures used to treat TB, and video-assisted thoracoscopic surgery, aminimally invasive technique, enables the removal of the diseased tissue. The surgical removal of one of the fivelung lobes is known as a lobectomy. When TB is limited to one lobe of the lung and cannot be adequately treatedwith medication alone, surgery is often undertaken. Candidates for lobectomy include patients with cavitary lesionslarger than 4 cm, a persistent cough, fever, hemoptysis, bronchopleural fistula, or localized abscess formation. Therisk of problems can be reduced with appropriate pre-operative assessment, surgical technique, and post-operativecare. The surgical removal of the complete lung is known as a pneumonectomy. It is normally saved for TB caseswhere medicine is ineffective and the disease has spread to affect a significant area of the lung. Pneumonectomymay be an option for patients who have severe cavitary lesions, extensive lung damage, considerable mainbronchus involvement, or consequences including bronchopleural fistula, severe hemoptysis, or localized abscessformation. Similar to lobectomy, the risk of problems can be reduced with good pre-operative assessment, surgicaltechnique, and post-operative care. A segment of a lung lobe is surgically removed, a procedure known as asegmentectomy or partial lobectomy. When TB is confined to a particular area of the lung and cannot be properlytreated with drugs alone, surgery may be an option. Segmentectomy may be beneficial for patients with a tinycavitary lesion, localized fibrosis, or a cavitary lesion that cannot be removed in the upper lobe of the lung or whoare unable to have more comprehensive surgery. Once more, minimizing the risk of problems can be achievedthrough good pre-operative assessment, surgical technique, and post-operative care.